One loop conformal invariance of the superstring in an AdS5 × S5 background - Vallilo, Brenno Carlini [UNESP] (Springer Nature, 2002)
It is proven that the pure spinor superstring in an AdS5 × S5 background remains conformally invariant at one loop level in the sigma model perturbation theory. © SISSA/ISAS 2003.
Keywords: Conformal Field Models in String Theory; Superstrings and Heterotic Strings